PELATIHAN TEKNIS PEMBUATAN KOMPOS JERAMI PADI DI DESA BANJARREJO KECAMATAN BATANGHARI KABUPATEN LAMPUNG TIMUR - Dulbari Dulbari; Yuriansyah Yuriansyah; Zainal Mutaqin; Lisa Erfa; I Gde Darmaputra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The level of fertility of paddy fields in Banjarrejo was decreasing, this is indicated by low rice productivity, fertilization response was leveling off, topsoil was shallow, and rice easy lodged. Fertility degradation of paddy fields occurs continuously. Factors that encourage the ongoing process of soil fertility degradation is a concept application of High External Input Agriculture (HEIA) on the cultivation of crops, especially rice. Rice straw can be used as an alternative to increase soil fertility and maintain the health of paddy field. Straw is the main product of rice cultivation in the form of organic fertilizer because its potential reaches 1.5 x grain yield. However, the potential that is available cheaply and easily and Lack of information and knowledge about straw causes many farmers not to utilize straw to the fullest. Straw is still regarded as an obstacle in tillage, where the nest mice, disease sources, and sources of dirt that must be cleaned. Farmers have not used it to be composted because many still do not have the skills to make it. State Polytechnic of Lampung has the role and responsibility to transfer technology that is beneficial to society especially in the case of making straw compost through the program of Community Service. Technical Training Composting of Rice Straw was conducted in Banjarrejo Village, Batanghari District, East Lampung Regency in April-September 2013. The use of straw compost in paddy fields can increase rice production while maintaining sustainable soil health.